Modèles politico-institutionnels et politique macroéconomique : analyse comparée de douze pays industrialisés 1960-1988 (Note) - Boismenu, Gérard (Études internationales, 1995)
This study evaluates the impact of institutional forms on public policies in areas related to the wage relationship. We suggest that four political-institutional models, based on the configuration of political and social forces and of Systems of interest representation are accompanied by differentiated macroeconomic policies. This relationship is studied, with regression equations, for many issues of macroeconomic policies (unemployment, inflation, public expenditure, social transfers, public finances, economic growth), for two periods (1960-1975,1976-1988) and for twelve countries (Canada, United States, France, Italy, Great Britain, West Germany, Belgium, Netherlands, Norway, Sweden, Austria, Denmark). It is possible to conclude that there is a relationship between models and shapes of macroeconomic policies, but there is not necessarily stability in political choices from one period to the other.